Pengaruh Struktur Kepemilikan dan Komisaris Independen terhadap Biaya Keagenan Perusahaan yang Masuk dalam Indonesia Most Trusted Companies - Pratiwi, Rafika; Yulianto, Arief (Universitas Negeri Semarang, 2016)
The divergences between shareholder and manager take agency cost. This study aims to investigate the influence of managerial ownership, institutional ownership, and independent commissoner on agency cost. Population of this study is firms that occur to Indonesia Most Trusted Companies Based on Investor 2007-2015, published by SWA business megazine. The number of sample is 106 observation data through purposive sampling method. Based on linier regression model, the result is managerial ownership and institutional ownership have no significant affect on agency cost, whereas independent commissioner has positif and significant affect on agency cost. So, if proportion of independent commissioner increase, agency cost will increase.